1996
DOI: 10.1021/jm9509105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray Crystal Structure of trans,cis-[Pt(OAc)2I2(en)]:  A Novel Type of Cisplatin Analog That Can Be Photolyzed by Visible Light to DNA-Binding and Cytotoxic Species in Vitro

Abstract: An original approach intended to facilitate the intratumoral activation of Pt(IV) diamines by illumination with visible light to form photolysis products that irreversibly bind to DNA and are cytotoxic to human cancer cells is reported. The novel Pt(IV) complex trans,cis-[Pt(OAc)2I2-(en)] was prepared by the acetylation of trans,cis-[Pt(OH)2I2(en)] with acetic anhydride in CH2-Cl2; trans,cis-[Pt(OH)2I2(en)] was synthesized by oxidation of [PtI2(en)] with 30% aqueous H2O2. trans,cis-[Pt(OAc)2I2(en)] crystallize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 52 publications
3
101
0
3
Order By: Relevance
“…This approach was initially tried with diiodido-Pt IV diamines, which were activated by visible light to cytotoxic species that platinated DNA, but the dark stability of the complexes in the presence of biological reducing agents such as GSH was poor and the complexes showed relatively high dark activity [11,12]. The first light-activated Pt IV complexes that were sufficiently stable in the presence of biological reducing agents were the diazido-Pt IV 2 ] developed by Sadler and co-workers [13].…”
Section: Photoactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was initially tried with diiodido-Pt IV diamines, which were activated by visible light to cytotoxic species that platinated DNA, but the dark stability of the complexes in the presence of biological reducing agents such as GSH was poor and the complexes showed relatively high dark activity [11,12]. The first light-activated Pt IV complexes that were sufficiently stable in the presence of biological reducing agents were the diazido-Pt IV 2 ] developed by Sadler and co-workers [13].…”
Section: Photoactivationmentioning
confidence: 99%
“…As in the case of the other two complexes, no reactions between either 4 or 6 and 5 -GMP took place in the dark. atomic absorption spectroscopy (AAS) [11,12] [24]. While all-trans-complexes 2 and 4 showed similar rates of photolysis (see §2c), photolysed 2 bound much more rapidly to ct-DNA than did the photolysed pyridine analogue 4, evidence that the pyridine ring has a substantial influence on the rate of reaction with ct-DNA [19].…”
Section: (A) Reactions With Nucleotidesmentioning
confidence: 99%
“…[134] The toxicity of trans,cis-[Pt(en)(OAc) 2 I 2 ] towards human bladder cancer cells is enhanced (by 35 %) when the treated cells are irradiated with light of l b 375 nm. It has been shown that visible light can induce the aquation of this complex followed by photoreductive platination of guanosine monophosphate, in contrast to the dihydroxo analogue.…”
Section: Photoactivationmentioning
confidence: 99%
“…[81] Cytotoxicity studies on TCCSUP human bladder cancer cells showed a small but statistically significant reduction in the IC 50 values and thus establish this complex as a light-sensitive prodrug. [82] The axial and equatorial anionic ligands allow some modulation of the general lead structure, and for trans,cis-[Pt-(N 3 ) 2 (OH) 2 (en)], it was found that their rate of photolysis closely parallels that of DNA platination, indicating that the photolysis products interact directly and rapidly with DNA. The response of the cell to photoactivation, however, was different to that induced by cisplatin, and although the formation of platinum(II) species is thought to follow photoactivation, this indicates a mechanism of action different from that of cisplatin.…”
Section: Photoactivable Platinum Prodrugsmentioning
confidence: 99%